Extraskeletal Ewing sarcoma of the parapharyngeal space with a unique translocation, t(19;22) (q13.4;q12.2) - Gloria Ramos-Rivera; Esther Adler; K.H. Ramesh; Bradley Schiff; Mark Suhrland; Samer Khader (Elsevier, 2016)
Extraskeletal Ewing sarcomas of the parapharyngeal space are extremely rare. It has been documented that Ewing sarcomas are morphologically and molecularly indistinguishable regardless of the tissue of origin. Around 85% of Ewing sarcomas are associated with translocation t(11;22)(q24.1;12.2) generating the EWSR1-FLI1 fusion oncoprotein. We report a case of an extraskeletal Ewing sarcoma arising in the parapharyngeal space with a unique translocation: t(19; 22) (q13.4;q12.2). To our knowledge this is the first case of an extraskeletal Ewing sarcoma exhibiting this translocation.